2021
DOI: 10.1002/bdd.2301
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically based pharmacokinetic modelling of acetaminophen in preterm neonates—The impact of metabolising enzyme ontogeny and reduced cardiac output

Abstract: In preterm neonates, physiologically based pharmacokinetic (PBPK) models are suited for studying the effects of maturational and non-maturational factors on the pharmacokinetics of drugs with complex age-dependent metabolic pathways like acetaminophen (APAP). The aim of this study was to determine the impact of drug metabolising enzymes ontogeny on the pharmacokinetics of APAP in preterm neonates and to study the effect of reduced cardiac output (CO) on its PK using PBPK modelling. A PBPK model for APAP was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Despite the numerous clinical pharmacokinetic studies of APAP and the emergence of MSI, only a few recent studies have investigated the liver zonation and whole-body distribution of APAP and its metabolites. These were carried out with MALDI-MSI, which is the most widely used MSI technique.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the numerous clinical pharmacokinetic studies of APAP and the emergence of MSI, only a few recent studies have investigated the liver zonation and whole-body distribution of APAP and its metabolites. These were carried out with MALDI-MSI, which is the most widely used MSI technique.…”
Section: Discussionmentioning
confidence: 99%
“…PBPK models have been successfully used for similar analyses where for example, the non-maturational impact of CYP2B6 genetic polymorphism and drug-drug interaction between efavirenz and lumefantrine alongside maturational changes in children was quantified [18]. More recently, Olusola et al demonstrated that the reduction in CO, as non-maturational parameter, did not significantly alter the acetaminophen pharmacokinetics in preterm neonates owing to immaturity of acetaminophen clearance pathways in preterms and the inherent low hepatic clearing capacity of acetaminophen [19].…”
Section: Introductionmentioning
confidence: 99%
“…PBPK models have been successfully used for similar analyses where, for example, the non-maturational impact of CYP2B6 genetic polymorphism and drug-drug interaction between efavirenz and lumefantrine alongside maturational changes in children was quantified [18]. More recently, Olusola et al demonstrated that the reduction in CO, as a non-maturational parameter, did not significantly alter the acetaminophen pharmacokinetics in preterm neonates owing to immaturity of acetaminophen clearance pathways in preterms and the inherent low hepatic clearance capacity of acetaminophen [19].…”
Section: Introductionmentioning
confidence: 99%